Food marketers at school: The challenge of trustworthiness in France (1900-2013). Issue 1 (3rd April 2019) - De Iulio, Simona
Abstract: This article focuses on the evolution of the relationships between food marketing communication and public education in France from the beginning of the twentieth century to the present. Firstly a broad historical reconstruction of the extension of food marketing communication to the sphere of public school is proposed. References to school in advertisements aimed at children in the postwar years are explored. The increase of various in-school marketing actions carried out by food companies from the 1960s to the end of the 1980s are examined such as the emergence of new forms of partnership between food marketers and French public schools following the introduction in the 1990s of the annual event La Semaine du Goût and the rapid generalization of new "educational" approaches. Secondly, the educational and normative character of recent food communication aimed at pupils, proposed by institutes and foundations linked with food multinationals, is analyzed and the ways in which these forms of in-school marketing try to converge with the principles of public health policy are elucidated.